Revisión sistemática de la efectividad de las table tops como tratamiento en pacientes que perdieron la dimensión vertical por bruxismo - Zevallos Portilla, Axel José (2025)
Bruxism is a condition characterized by involuntary grinding or clenching of the teeth, usually during sleep. It is divided into two types: centric (clenched teeth) and eccentric (grinding teeth). This problem can have negative effects on oral and general health, such as tooth wear, jaw pain, headaches, sleep disorders, and temporomandibular joint disorders. The etiology of bruxism is multifactorial with genetic, psychological, biomechanical, and neurophysiological influences. Risk factors include stress, anxiety, tooth root disorders, alcohol and drug use, and certain sleep disorders such as obstructive sleep apnea. The diagnosis of bruxism is primarily made by clinical observation and patient history, although electromyography and recordings of occlusal activity during sleep may also be used. Treatment of bruxism usually involves a multidisciplinary approach targeting the cause and symptoms. This may include behavioral therapy, physical therapy, braces, medications, and stress management. A review of the literature on bruxism covers aspects such as epidemiology, pathophysiology, diagnostic methods, treatment options, and long-term outcomes. A large number of clinical and experimental studies have been conducted to better understand this disease and develop effective treatment strategies. Active areas of research include identifying biomarkers, developing more targeted therapies, and evaluating preventative interventions. Overall, more research is needed to improve the understanding and treatment of bruxism, especially as it is associated with other psychological and sleep disorders. Our scientific collaboration efforts generated 456 identifications in the initial phase. Using filters to exclude scientific articles may have resulted in 306 articles being discarded over time. As if 102 were removed because I don't know if access is free or open. After reading the abstract, it was decided to discard 19 articles for not providing relevant data, and after reading the summary, 21 articles were discarded, with a total of 8 articles viable for analysis.